Comparison of Battery Electric Power Consumption in a Fingerprint System or a Motor Manual Lock System - Amalia, Sitti; Andari, Rafika; Arif, Jumadi (PROtek : Jurnal Ilmiah Teknik Elektro, 2023)
Motorcycle security systems using fingerprint sensors are needed to avoid theft because of their high level of security compared to manual systems. This study underscores the importance of using this fingerprint sensor for motorcycle security. The formulation of the problem in this study is how much electricity is required in the motorcycle battery for this fingerprint security system. This system uses various components, such as the R503 fingerprint sensor, Arduino Uno, buzzer, 4-channel relay, ignition key, and motorcycle starter. Testing of this system is performed by inserting a finger in a wet, oily, dusty, or normal condition, and the result is that this sensor is capable of detecting the entire condition of the finger. Attempts to start a motorcycle with all ten fingers showed that the left index finger started faster under normal conditions, in 1.55 seconds compared to the manual method, which took 2.05 seconds longer. It also measures power consumption and calculates how long the battery can power this device. The result is that the battery can power this device for 180 hours without interruption